Hospital Wastewater-Source of Specific Micropollutants, Antibiotic-Resistant Microorganisms, Viruses, and Their Elimination - Mackuľak, Tomáš; Cverenkárová, Klára; Vojs Staňová, Andrea; Fehér, Miroslav; Tamáš, Michal; Škulcová, Andrea Bútor; Gál, Miroslav; Naumowicz, Monika; Špalková, Viera; Bírošová, Lucia (Antibiotics (Basel, Switzerland), 2021)
Municipal wastewaters can generally provide real-time information on drug consumption, the incidence of specific diseases, or establish exposure to certain agents and determine some lifestyle consequences. From this point of view, wastewater-based epidemiology represents a modern diagnostic tool for describing the health status of a certain part of the population in a specific region. Hospital wastewater is a complex mixture of pharmaceuticals, illegal drugs, and their metabolites as well as different susceptible and antibiotic-resistant microorganisms, including viruses. Many studies pointed out that wastewater from healthcare facilities (including hospital wastewater), significantly contributes to higher loads of micropollutants, including bacteria and viruses, in municipal wastewater. In addition, such a mixture can increase the selective pressure on bacteria, thus contributing to the development and dissemination of antimicrobial resistance. Because many pharmaceuticals, drugs, and microorganisms can pass through wastewater treatment plants without any significant change in their structure and toxicity and enter surface waters, treatment technologies need to be improved. This short review summarizes the recent knowledge from studies on micropollutants, pathogens, antibiotic-resistant bacteria, and viruses (including SARS-CoV-2) in wastewater from healthcare facilities. It also proposes several possibilities for improving the wastewater treatment process in terms of efficiency as well as economy.
Keywords: hospital wastewater treatment; pharmaceuticals; antibiotic-resistant microorganisms; SARS-CoV-2; antimicrobial resistance genes